Irrigated Needle Ablation Compared With Other Advanced Ablation Techniques for Failed Endocardial Ventricular Arrhythmia Ablation. (16th June 2021) - Narui, Ryohsuke; Tanigawa, Shinichi; Nakajima, Ikutaro; Tokutake, Kenichi; Nakamura, Tomofumi; Richardson, Travis; Salloum, Joseph; Sapp, John; Kanagasundram, Arvindh; Tedrow, Usha; Stevenson, William
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Options when endocardial ventricular arrhythmia ablation fails include epicardial, simultaneous 2-site unipolar radiofrequency (SURF), and transcoronary ethanol ablation. Recently, investigational needle ablation has also been used, but how it compares to other advanced methods is not clear. This study sought to compare outcomes and complications for needle ablation versus other advanced ablation techniques in patients with structural heart disease, ventricular arrhythmia, and failed endocardial ablation. Methods: We retrospectively reviewed 136 procedures in 119 consecutive patients with structural heart disease (excluding arrhythmogenic right ventricular cardiomyopathy) who failed endocardial ablation and underwent ablation with either an investigational needle catheter (27 gauge, single end hole) or with other advanced techniques including epicardial, SURF or transcoronary ethanol ablation. Results: Of 136 procedures, needle ablation was performed in 58 procedures. In the remaining 78 procedures, 65 were epicardial ablation, including 10 with SURF ablation from endocardial and epicardial sites, 7 with SURF from both sides of the septum, one SURF and transcoronary ethanol ablation, and 5 transcoronary ethanol ablation procedures. Acute outcomes, 6-month ventricular arrhythmia recurrence, and mortality rates were not different between the 2 groups (49% versus 55%, P =0.54, 45% versus 46%, P =1.00, and 4% versus 3%, P =1.00, respectively). There were 22 major complications observed in 22 procedures with pericardial bleeding occurring less frequently with needle ablation (1.7% versus 12.8%, P =0.02). Conclusions: Ablation with an irrigated needle catheter compares favorably to other advanced ablation techniques.